Credit allocation, capital requirements and procyclicality - Esa Jokivuolle; Ilkka Kiema; Timo Vesala (Bank of Finland, 2009)
Although beneficial allocational effects have been a central motivator for the Basel II capital adequacy reform, the interaction of these effects with Basel II's procyclical impact has been less discussed. In this paper, we investigate the effect of capital requirements on the allocation of credit and its interaction with procyclicality, and compare Basel I and Basel II type capital requirements. We consider competitive credit markets where entrepreneurs of varying ability can apply for loans for one-period investment projects of two different risk types. The risk of a project further depends on the state of the economy, modelled as a two-state Markov process. In this type of setting, excessive risk taking typically arises because higher-type borrowers cross-subsidize lower-type borrowers via a pricing regime based on average success rates. We find that risk-based capital requirements (such as Basel II) alleviate the cross-subsidization effect and can be chosen so as to implement first-best allocation. This implies that the ensuing reduction in the proportion of high-risk investments may mitigate the procyclical effect of Basel II on economic activity. Moreover, we find that optimal risk-based capital requirements should be set lower in recessions than in normal times. Our simulations show that when measured by either cumulative output or output variation, Basel II type capital requirements may actual be slightly less procyclical than flat capital requirements. The biggest reduction in procyclicality is however achieved with optimal risk-based capital requirements which are considerably higher than Basel II requirements and which are adjusted downwards in recession periods.
URN:NBN:fi:bof-20140807198
Keywords: D41; D82; G14; G21; G28; 330; Basel II; bank regulation; capital requirements; credit risk; procyclicality